2022
DOI: 10.5599/jese.1220
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of corrosion protection methods in reinforced concrete by artificial neural networks and fuzzy logic

Abstract: In this study, the effect of protection methods regarding the corrosion decrement of steel in concrete was simulated by artificial neural networks (ANNs) and fuzzy logic (FL) approaches. Hot dip galvanizing as a protective coating, Ferrogard 901 corrosion inhibitor, a pozzolanic component, such as fly ash (FA) and micro-silica (MS), and eventually rebar AISI-304 were employed in concrete. Reinforced concrete samples were held under impres­sed voltage of 30 V in 3.5 % NaCl electrolyte for 350 hours toward a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…The diffusive travel of corrodents is resisted by the concrete cover, typically taken to be 30-50 mm. In several studies [49][50][51][52][53][54], corrosion damage has been reported to be responsible for the reductions in service life and the ultimate capability of RC structures. Consequently, the construction industry, seeking solutions to this durabi in steel RCs, has been considering methods for the corrosion protection of ments.…”
Section: Background 21 Steel Deterioration In Rc Beamsmentioning
confidence: 99%
“…The diffusive travel of corrodents is resisted by the concrete cover, typically taken to be 30-50 mm. In several studies [49][50][51][52][53][54], corrosion damage has been reported to be responsible for the reductions in service life and the ultimate capability of RC structures. Consequently, the construction industry, seeking solutions to this durabi in steel RCs, has been considering methods for the corrosion protection of ments.…”
Section: Background 21 Steel Deterioration In Rc Beamsmentioning
confidence: 99%